2007
DOI: 10.1002/ijc.23182
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of wogonin in both estrogen receptor‐positive and ‐negative human breast cancer cell lines in vitro and in nude mice xenografts

Abstract: Wogonin is a plant monoflavonoid which has been reported to inhibit cell growth and/or induce apoptosis in various tumors. Herein, we investigated the in vitro and in vivo anticancer effects and associated mechanisms of wogonin in human breast cancer. Effects of wogonin were examined in estrogen receptor (ER)-positive and -negative human breast cancer cells in culture for proliferation, cell cycle progression, and apoptosis. The in vivo effect of oral wogonin was examined on tumor xenograft growth in athymic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 34 publications
3
65
0
Order By: Relevance
“…Consequently, nitric oxide synthesis and prostaglandin E2 production are inhibited Kim et al, 2001). In addition, it has been reported that wogonin posesses anticancer activities in several cancer cells, including myelogenous leukemia cells , hepatomacellular carcinoma cells (Wang et al, 2006a), breast cancer cells (Chung et al, 2008), murine sacrcoma S 180 cells (Wang et al, 2006b) and bladder cancer cells (Ikemoto et al, 2000). Interestingly, wogonin has no effect on inducing apoptosis in PBMCs and fibroblasts (Liu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, nitric oxide synthesis and prostaglandin E2 production are inhibited Kim et al, 2001). In addition, it has been reported that wogonin posesses anticancer activities in several cancer cells, including myelogenous leukemia cells , hepatomacellular carcinoma cells (Wang et al, 2006a), breast cancer cells (Chung et al, 2008), murine sacrcoma S 180 cells (Wang et al, 2006b) and bladder cancer cells (Ikemoto et al, 2000). Interestingly, wogonin has no effect on inducing apoptosis in PBMCs and fibroblasts (Liu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Wogonin has been shown to have antioxidant, antiviral, antithrombotic and anti-inflammatory activities in both in vitro and in vivo studies (26)(27)(28)(29). The anticancer activity of wogonin is demonstrated by inducing apoptosis in cancer cells and suppressing growth of human cancer xenografts in vivo (30,31). Wogonin has also been tested to kill cancer cells in combination with other chemotherapeutics (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Wogonin (5,7-dihydroxy-8-methoxyflavone, C 16 H 12 O 5 ) is one of the active ingredients extracted from the roots of Scutellaria baicalensis Georgi. It has been reported that wogonin induced apoptosis in many tumor cells such as human breast cancer cell lines (8), prostate cancer cells (10), hepatocellular carcinoma SK-HEP-1 cells (11), promyeloleukemic cells (10) cancer A2780 cells (12) and it suppressed tumor cells growth (13).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids, one of the most common active ingredients of medicinal herbs, possess pharmacological properties including anti-infammatory (5,6), antioxidant (7), and antitumor (8,9) activities. Wogonin (5,7-dihydroxy-8-methoxyflavone, C 16 H 12 O 5 ) is one of the active ingredients extracted from the roots of Scutellaria baicalensis Georgi.…”
Section: Introductionmentioning
confidence: 99%